2014
DOI: 10.15252/emmm.201404046
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term therapeutic silencing of miR‐33 increases circulating triglyceride levels and hepatic lipid accumulation in mice

Abstract: Plasma high-density lipoprotein (HDL) levels show a strong inverse correlation with atherosclerotic vascular disease. Previous studies have demonstrated that antagonism of miR-33 in vivo increases circulating HDL and reverse cholesterol transport (RCT), thereby reducing the progression and enhancing the regression of atherosclerosis. While the efficacy of short-term anti-miR-33 treatment has been previously studied, the long-term effect of miR-33 antagonism in vivo remains to be elucidated. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 31 publications
3
96
3
Order By: Relevance
“…In fact, therapies targeted to raise HDL-cholesterol are effective in treating dyslipidemia and disease progression (Rayner et al 2010, Waksman et al 2010. Nevertheless, consistent with our findings, recent studies have shown that chronic increased HDL-cholesterol levels produced by some of these therapies, such as long-term therapeutic silencing of miR-33 in mice challenged with a high-fat diet, produced moderate hypertriglyceridemia and hepatic steatosis (Goedeke et al 2014). Altogether, these data suggest that modulation of lipases that develops with 'toxic' dyslipidemia (hypercholesterolemia, hypertriglyceridemia and high FFA) promote hepatic steatosis and NAFLD.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, therapies targeted to raise HDL-cholesterol are effective in treating dyslipidemia and disease progression (Rayner et al 2010, Waksman et al 2010. Nevertheless, consistent with our findings, recent studies have shown that chronic increased HDL-cholesterol levels produced by some of these therapies, such as long-term therapeutic silencing of miR-33 in mice challenged with a high-fat diet, produced moderate hypertriglyceridemia and hepatic steatosis (Goedeke et al 2014). Altogether, these data suggest that modulation of lipases that develops with 'toxic' dyslipidemia (hypercholesterolemia, hypertriglyceridemia and high FFA) promote hepatic steatosis and NAFLD.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been reported that long-term silencing of miR-33 resulted in an unexpected increase in circulating triglyceride levels and lipid accumulation in the liver. 65 Because our genetic KO mice were equivalent to permanent inhibition, long-term inhibition of miR-33 can cause harmful side effects. To utilize the protective effect of miR-33 inhibition, further research is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies have demonstrated the efficacy of anti-miR-33 therapy for raising plasma HDL cholesterol levels and reducing the atherosclerotic plaque burden in both rodents and nonhuman primates (41,43,(56)(57)(58)(59). However, the increased risk for development of hepatic steatosis observed in some of these studies emphasizes the poten- tial for unintended effects of anti-miR-33 therapy (60,61). For this reason, understanding the role of miR-33 in other metabolic tissues, such as WAT, is of critical importance.…”
Section: Mir-33b Expression Is Induced During Differentiation Of Humamentioning
confidence: 99%